Food, Eating, and Narrativization of Identity in Margaret Atwood’s Lady Oracle - BEZDOODE, Zakarya; RAHIMI, Sarisa (Anafora, 2023)
The present paper seeks to explore the significance of eating in the process of identity formation in Margaret Atwood’s Lady Oracle and its effects upon Joan, the female protagonist of the novel. Based on the findings of Susie Orbach (1946), Joan appears to have developed an ambivalent relationship with food from a very early age. Once she decides to lose weight and turn into what the society has always demanded her to look like, she develops an identity crisis which is reflected in her literary production. There are several barriers in the process of Joan’s identity formation that reveal themselves later in her narratives as an author. The focus of this study is to shed light on this problematic process of being a female author coping with nutritional insecurities.